2007
DOI: 10.1126/science.1146711
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Linked Genetic Influence on Caste Determination in a Termite

Abstract: The most ecologically successful and destructive termite species are those with both a nymph caste and an irreversibly wingless worker caste. The early developmental bifurcation separating these castes is widely accepted to be strictly environmentally determined. We present evidence that genotype also influences this process. Offspring from four different crosses of nymph- and worker-derived secondary reproductive individuals had strongly differentiated caste and sex ratios, despite uniform rearing conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
96
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 20 publications
5
96
2
Order By: Relevance
“…The role of development in caste differentiation is well studied among species that are obligately eusocial [6][7][8][9][10][11][12][13]. Although these studies have been extremely valuable, insights into how solitary ground plans were first modified may be obscured by the novel evolutionary pressures arising from obligate reproductive castes [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The role of development in caste differentiation is well studied among species that are obligately eusocial [6][7][8][9][10][11][12][13]. Although these studies have been extremely valuable, insights into how solitary ground plans were first modified may be obscured by the novel evolutionary pressures arising from obligate reproductive castes [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Even though recent studies revealed genetic influences on caste determination in social insects (reviewed in ref. 26), female caste fate is primarily influenced by environmental factors in most species studied (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). In ants, several studies suggested that maternal factors such as temperature or queen age may affect caste determination (40)(41)(42)(43)(44).…”
mentioning
confidence: 99%
“…There were extreme differences in the proportions of caste and sex between offspring from different combinations of parents, indicating that genetic factors influenced the developmental commitment to the worker or nymph caste. We also showed that almost all of the offspring produced through parthenogenesis developed into nymphs when they were reared only with tending workers, while 24% of parthenogenetically-produced offspring differentiated into workers when reared with an additional pair of nymphoids (Hayashi et al, 2007). This suggests that the existence of pairs of nymphoids can influence the developmental trajectory of larvae.…”
mentioning
confidence: 67%
“…Our previous studies on the Japanese subterranean termites Reticulitermes speratus (Hayashi et al, 2007), R. okinawanus, R. kanmonensis, and R. yaeyamanus (Kitade et al, 2011) provided evidence for genetic influences on caste determination of larvae. In Reticulitermes, each individual becomes either a nymph or a worker after two larval instar stages (Buchli, 1958;Shimizu, 1970;Takematsu, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation